O15: DISRUPTION OF THE BLOOD‐SPINAL CORD BARRIER PREDICTS PERMANENT PARAPLEGIA AFTER THORACOABDOMINAL AORTIC ANEURYSM REPAIR. (27th April 2021) - Kelly, J; Patel, A; Onadim, I; Abisi, S; Bell, R; Tyrrell, M; Sallam, M; Salih, M; Mayr, M; Bradbury, E; Cho, J; Gworzdz, A; et al.
Abstract: Introduction: Paraplegia post‐thoracoabdominal aortic aneurysm (TAAA) repair remains both a devastating and poorly understood complication. We related temporal changes in cellular and protein composition of cerebrospinal fluid (CSF) to neurological outcomes after TAAA repair to gain mechanistic insights driving paraplegia. Method: Patients undergoing TAAA repair (open or endovascular) with a CSF drain were prospectively recruited between 2016‐2018. CSF was collected pre‐operatively and 24‐hourly until removal. Daily neurological examinations were performed by blinded neurologists to the study. CSF cell content was characterised by flow cytometry and proteome analysed by tandem‐mass‐tag proteomics. An in‐vivo rat model was modified using 15 minutes of aortic occlusion to produce consistent paraplegia. Rats were analysed neuro‐behaviourally and histologically. Result: CSF was analysed from 52 patients ( age: 70.27+/‐11.4; 66% male; open (n=9), endovascular (n=43 )). 12 developed paraplegia of whom 5 remained permanently‐paraplegic. Demographics were comparable between paraplegics, those who recovered and without post‐op neurology. Permanent paraplegia was associated with a significant infiltration of CSF CD45 + leucocytes ( P<0.0001 ). Levels of ADVS‐1 was >3‐fold higher in permanent‐paraplegics CSF versus those who recovered ( P=0.0008 ). ADVS‐1 >15ng/ml predicted permanent paraplegia with 100% specificity. Pre‐treatment with ADVS‐1 inhibition significantly improved walking (<0.001 ) and increased astrocytic staining in the lateral corticospinal, reticulospinal and rubrospinal tracts versus controls ( P=0.03, 0.04, 0.04 respectively ). Conclusion: Permanent paraplegia is associated with shedding of ADVS‐1 from parenchymal cord into CSF and blood/spinal‐cord barrier disruption leading to cord oedema/leucocyte infiltration. Pre‐treatment with ADVS‐1 inhibition led to neurobehavioural and histological improvements offering translational hope for this devastating complication. Take‐home message: ADVS‐1 is a novel biomarker of paraplegia where accurate biomarkers have proven challenging but more importantly it has proven a therapeutic target with genuine translational potential.